The Impact of Non-Cognitive Skills and Risk Preferences on Rural-to-Urban Migration: Evidence from Ukraine - Sinem H. Ayhan; Kseniia Gatskova; Hartmut Lehmann (Institute of Labor Economics (IZA), 2017)
This paper provides evidence on the impacts of non-cognitive skills and attitudes towards risk on the decision to migrate from rural to urban areas. Our analysis is based on a unique four-wave panel of Ukrainian Longitudinal Monitoring Survey for the period between 2003 and 2012. Adopting the Five Factor Model of personality structure, and using it in the evaluation of non-cognitive skills, our results suggest that such personality traits as openness to new experience and the willingness to take risks increase the probability of migration. On the other hand, the non-cognitive skills conscientiousness and extraversion are found to be negatively associated with the propensity to migrate. The effects are statistically and quantitatively significant, and mainly driven by movements from rural areas into cities. Our results are robust to several sensitivity checks, including tests for reverse causality.
Keywords: J61; D03; D81; R23; 330; migration; non-cognitive skills; Big Five; risk attitudes